2022
DOI: 10.4314/ahs.v22i2.14s
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone-based Intervention to promote un-interrupted HIV treatment during the COVID-19 pandemic

Abstract: Introduction: Keeping HIV-infected adults away from the health care system during the COVID-19 travel restrictions, presents a challenge to HIV treatment adherence. Methods: This study focused on the initial two phases where Phase 1 designed a Makerere College of Health Sciences (MakCHS) Unstructured Supplementary Service Data (USSD)-based application; and Phase 2 piloted patient enrolment onto the application and determined the feasibility of remote follow-up of patients receiving long-term antiretrovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The feasibility of remote follow‐up of patients receiving long‐term ART was determined, which showed that 112 patients receiving ART at Mulago Immune Suppression Syndrome clinic in Kampala enrolled in the MakCHS Health app. Up to 89 (80%), patients used the app to access COVID‐19 vaccination and other personal needs that required a clinician [ 18 ]. Another randomized controlled pilot trial in Korea evaluated the effects of a self‐management program using a mobile app (Health Manager) on self‐management outcomes among PLHIV in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of remote follow‐up of patients receiving long‐term ART was determined, which showed that 112 patients receiving ART at Mulago Immune Suppression Syndrome clinic in Kampala enrolled in the MakCHS Health app. Up to 89 (80%), patients used the app to access COVID‐19 vaccination and other personal needs that required a clinician [ 18 ]. Another randomized controlled pilot trial in Korea evaluated the effects of a self‐management program using a mobile app (Health Manager) on self‐management outcomes among PLHIV in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…A venture into high tech medicine 8 , PhD training 9 , and quick response to pandemics [10][11][12][13] highlights Makerere's diverse roles. We give the readers a glimpse into surgery 14 , refugee health 15 and eyecare 16 as we conclude themes of this special issue.…”
Section: Editor's Choice!mentioning
confidence: 99%